Oligarchic Media Ownership and Polarized Television Coverage in Indonesia’s 2014 Presidential Election - Prasakti Ramadhana Fahadi (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2019)
It has been argued that the media ownership is an influential factor determining the content production and performance of the media. However, knowledge about the characteristics of the media ownership and its impacts on the coverage of general election by the media has been less researched. Judging by such developments, this work raises the following question: how did the oligarchic ownership of the Indonesian news television channels determine the ways in which they covered two candidates who ran for president in 2014? By selecting TV One and Metro TV as a case study, this work extracts reports on the ways in which these news TV channels have produced news content related to the 2014 general election using qualitative and thematic content analyses. The findings are as follows: In the 2014 Indonesian presidential election, both TV One and Metro TV failed to comply with the ideal journalistic principles of covering both sides, objective and balanced reporting, as required by the Indonesian Broadcasting Commission, while broadcasting news about the two presidential candidates. Instead, the television stations preferred to broadcast the polarized news coverage of the presidential candidates. TV One appeared to show more support for the Prabowo-Hatta Rajasa presidential candidate pair, while Metro TV favoured the Joko Widodo-Jusuf Kalla presidential candidate pair. This suggests that oligarchic media ownership strongly influenced the content production and performance of these news TV channels. They were used by oligarchs who have the media company to convey their personal political agendas in the hope that it will influence, or even set, the public’s agenda.